Young children understand how social connections affect what people know about each other - Aaron Chuey; Julian Jara-Ettinger; Hyowon Gweon (Proceedings of the National Academy of Sciences, 2026)
An unwritten expectation in our everyday social interactions is that intimate personal information about someone—“insider knowledge”—is usually confined within close relationships. For example, it would be odd, or even unsettling, if a stranger knew about your favorite movie. Such expectations about who knows what about whom constitute a cornerstone of complex social behavior, but much remains unknown about their cognitive underpinnings and developmental origins. Drawing on parental report (Study 1) as well as a novel experimental approach using controlled but naturalistic videochat conversations (Study 2 & 3), we find that 4- to 5-y-old children have an abstract, theory-like understanding of how social connections give rise to interpersonal knowledge. Self-report, facial expressions, and memory errors provide converging evidence that children were surprised when someone possessed insider knowledge that is misaligned with their relationships, such as a stranger knowing their favorite food (Study 2a) or their own parent knowing a stranger’s favorite movie (Study 2b). Children also generated coherent ad-hoc explanations about how someone might have acquired that knowledge, appealing to either first-hand observations or second-hand sources (Study 3). These findings demonstrate an early-emerging understanding of how individual minds are shaped in the context of their social networks, supporting a precocious ability to detect and explain anomalies in what people know about each other in real-time conversations. The current work also opens possibilities for leveraging open-ended online interactions to study social cognition without compromising experimental control.